The Influence of Complaint Response Quality, Hospital Image, and Per-ceived Value on Referral Intention - Christian Mayumi Semeru; Rina Anindita; Mohamad Reza Hilmy (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Patient referral intention is an important indicator of hospital sustainability and competitiveness. This study aimed to analyze the influence of complaint response quality, hospital image, and perceived value on referral intention at a Type C public hospital in Jakarta. A quantitative cross-sectional design was employed using a survey of patients who had received healthcare services at the hospital. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).The results showed that complaint response quality had a significant positive effect on both hospital image and perceived value. Patients who perceived complaint handling as responsive, fair, and effective tended to develop a more favorable image of the hospital and higher perceived value. Furthermore, hospital image and perceived value significantly influenced referral intention. Among the variables examined, hospital image demonstrated the strongest effect on patients’ willingness to revisit and recommend the hospital to others. The findings also indicated that perceived value partially mediated the relationship between complaint response quality and referral intention.These results suggest that improving complaint management, strengthening a positive hospital image, and enhancing patient value perceptions are essential strategies for increasing referral intention. Hospital managers should prioritize responsive complaint handling and continuous service quality improvement to build patient trust and loyalty. This study contributes to healthcare management literature by providing empirical evidence on factors affecting referral intention in public hospital services.